AN INTEGRATED APPROACH TO CHARACTER EDUCATION IN ISLAMIC BOARDING SCHOOLS: A CASE STUDY AT HIDAYATUL FAIZIEN ISLAMIC BOARDING SCHOOL, GARUT - Sopandi, Ipan; Sumantri, Suryana; Saefurridjal, Achmad; Helmawati, Helmawati (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to analyse the implementation of character education at Hidayatul Faizien Islamic Boarding School in Garut which combines formal and non-formal curriculum in shaping students' character. This research uses a qualitative approach, observation methods, and in-depth interviews with pesantren administrators and teachers. The results showed that character education at Hidayatul Faizien Islamic Boarding School was carried out through an exemplary approach, strengthening moral values, and disciplinary training. The ustadz acts as a behaviour model that shows discipline and responsibility, which is then imitated by the santri in everyday life. In addition, special programmes such as Ta'lim wa Tarbiyah and cooperation activities strengthen moral and social values in santri. The effect of this character education is seen in the social attitudes of santri, who are more tolerant, empathetic, and have high social responsibility. In conclusion, an integrated approach that includes moral knowledge, feelings, and actions at Hidayatul Faizien Islamic Boarding School has holistically shaped students' character. This study suggests that the character education model in this pesantren can be applied in other educational institutions to build the character of the younger generation with integrity.